Meniscus Graft Augmentation for a Midsubstance Tear of the Medial Collateral Ligament during Total Knee Arthroplasty - Sun, Changjiao; Rong, Wei; Du, Ruiyong; Wu, Sha; Liu, Pu; Zhang, Wei; Cai, Xu (The Journal of Knee Surgery, 2020)
Multiple surgical techniques exist to repair iatrogenic medial collateral ligament (MCL) injury during total knee arthroplasty (TKA). The objective of the study is to confirm the clinical effectiveness of meniscus transfer for treatment of iatrogenic MCL midsubstance transection in which remaining MCL is of poor quality, and there is a persistent gap between both ligament ends during TKA. From January 2015 to November 2019, we treated 11 patients with MCL injuries of 882 primary TKAs by meniscus transfer. Another 24 primary TKAs were recruited as a control group. The two groups of patients were comparable for age, gender, body mass index (BMI), Knee Society scoring (KSS), knee function score (KFS), and type of prosthesis comparison without significant difference (p > 0.05). We reviewed the patient's stability, as well as objective measures such as KSS and KFS scores, physical examinations, and radiographs. No patient of either group reported impaired wound healing, joint instability on physical examination, pain, radiographic changes, signs of loosening, and other complications. At the final follow-up, there was no significant difference in terms of KSS (p = 0.780) and KFS (p = 0.612) between the injury group and control group at last follow-up. X-ray image review showed no prosthesis loosening or subsidence for both groups. Based on these results, we are cautiously optimistic that midsubstance transections in which the quality of remaining tendon is weak, there is suspicion of stretching, or there is a persistent gap between both ligament ends that can be reconstructed with meniscus autograft transfer augmentation and an unconstrained implant.
Keywords: total knee arthroplasty; medial collateral ligament injury; meniscus; constrained implant; Knee Society score